Supply cost minimization for distribution systems with multi-cost multi-point supply through network reconfiguration - Morales, Ryan S. (2008)
The emergence of electricity markets provided distribution utilities with opportunities to provide more reasonable cost of electricity for the customers. A distribution utility can operate its electrical system at a configuration so that the costs for the supply of the loads are at minimum. This paper has developed an algorithm for reconfiguring distribution systems having multiple supply points with different nodal prices to minimize total supply costs subject to a system loss limit. The method starts from a weakly meshed configuration followed by series of linear economic dispatch runs to find optimal supply mix. The supply optimization terminates when the system loss level is reached, after which, a heuristic based switch opening procedure is performed. The system loss is modeled as a linear combination of power injections whose coefficients vary for every economic dispatch run and opening of switch in the system. The solution is reached when no electrical loops exist in the distribution network. An important contribution of the paper was the implementation of the proposed algorithm to an actual distribution network characterized by looped sub-transmission system. The resulting optimal configuration reduced both the supply cost and system losses with the reductions further improved upon identification and correction of maximum power limit constraint of a particular supply node. The paper also showed relationship among parameters such as the supply injections, nodal prices, system loss and supply cost.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman.
Keywords: Electric power consumption -- Forecasting -- Mathematical models